Factores que afectan la calidad de leche cruda , en la rutina de ordeño mediante conteo de ufc y ccs en dos veredas del municipio de Supatá Cundinamarca (2022)
It is important to know the quality of the milk produced in Colombia. For Therefore, an excellent milking routine occurs depending on good hygiene practices and management of each animal, from entering the milking parlor, to driving the milk to the tank Cooling. (Kruze, J. 1998). The producer must have analysis tools that help obtain good quality milk by complying with hygienic and established for the region and the country, in order to obtain better economic benefits. (Delgado, Rivera, Duque & Guevara, 2014).